2016
DOI: 10.3390/molecules21030285
|View full text |Cite|
|
Sign up to set email alerts
|

Biofuels and Their Co-Products as Livestock Feed: Global Economic and Environmental Implications

Abstract: Abstract:This review studies biofuel expansion in terms of competition between conventional and advanced biofuels based on bioenergy potential. Production of advanced biofuels is generally more expensive than current biofuels because products are not yet cost competitive. What is overlooked in the discussion about biofuel is the contribution the industry makes to the global animal feed supply and land use for cultivation of feedstocks. The global ethanol industry produces 44 million metric tonnes of high-quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 72 publications
1
53
0
6
Order By: Relevance
“…The dependency on fossil fuel based energy sources leads to the global problem of pollution and climate change [16,17]. The quest to find alternative resources for petroleum-based products (especially for transportation) has been the major impetus to produce bioenergy from renewable resources [18]. In this context, use of waste biomass in a biorefinery could be a potential alternative.…”
Section: Waste Biomass: Veiled Opportunitymentioning
confidence: 99%
See 1 more Smart Citation
“…The dependency on fossil fuel based energy sources leads to the global problem of pollution and climate change [16,17]. The quest to find alternative resources for petroleum-based products (especially for transportation) has been the major impetus to produce bioenergy from renewable resources [18]. In this context, use of waste biomass in a biorefinery could be a potential alternative.…”
Section: Waste Biomass: Veiled Opportunitymentioning
confidence: 99%
“…The competition among traditional and advanced biofuels will affect their large-scale production since they depend largely upon the limited land resources, crops (food/non-food), and lignocellulosic wastes. An EF strategy can contribute both to a more efficient energy production and livestock feed (indirectly to food supply) with the use of the byproducts of bioethanol production [18]. An integrative process was also developed combining bioethanol production along with MEC to produce hydrogen with concurrent degradation of phenolic compounds and its derivatives (furfurals) from the by-products of bioethanol (Figure 3).…”
Section: Alcoholsmentioning
confidence: 99%
“…The diversion of land previously used in food production towards energy crops (Land Use Change-LUC) is considered to be one factor behind those food price hikes [22][23][24][25], mainly because of its impacts on Greenhouse Gas (GHG) and wider ecosystems. When demand for biofuels increases, farmers will have an incentive to meet this demand by producing more feedstock for biofuels production.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of SBP (10%) into a poultry diet based on corn, sunflower meal, barley, and wheat increases its water-holding capacity (+30%) and its swelling capacity (+15%) . Its use in goose diets has no detrimental effects on geese reared for meat production (Arslan, 2003(Arslan, , 2005 and could help mitigate the environmental consequences of both the animal production system (Mackenzie et al, 2016) and the biofuel industry (Popp et al, 2016). Additionally, Arroyo et al (2015) showed that SBP incorporation (10%) in a complete pelleted diet for geese reared for foie gras production tended to increase the crop volume of the birds (+8%).…”
Section: Introductionmentioning
confidence: 99%